Surface tension and its role for vertical wet etching of silicon - Brockmeier, A; Rodriguez, F J Santos; Harrison, M; Hilleringmann, Ulrich (Journal of Micromechanics and Microengineering)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Mechanics of Materials; Electronic; Optical and Magnetic Materials

IEEE 1599 for Live Musical and Theatrical Performances - Baraté, Adriano; Haus, Goffredo; Ludovico, Luca Andrea; Mauro, Davide Andrea (Journal of Multimedia)
Keywords: Electrical and Electronic Engineering; Artificial Intelligence; Media Technology

Effect of shear on vesicle and lamellar phases of DDAB/lecithin ternary systems - Youssry, Mohamed; Coppola, Luigi; Nicotera, Isabella; Ar, Gönül; Schmidt, Claudia (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Solution processed inverter based on zinc oxide nanoparticle thin-film transistors with poly(4-vinylphenol) gate dielectric - Wolff, K.; Hilleringmann, Ulrich (Solid-State Electronics)
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Exposure of [MnIII6CrIII]3+ single-molecule magnets to soft X-rays: The effect of the counterions on radiation stability - Helmstedt, Andreas; Sacher, Marc; Gryzia, Aaron; Harder, Alexander; Brechling, Armin; Müller, Norbert; Heinzmann, Ulrich; Hoeke, Veronika; Krickemeyer, Erich; Glaser, Thorsten; Bouvron, Samuel; Fonin, Mikhail (Journal of Electron Spectroscopy and Related Phenomena)
Keywords: Physical and Theoretical Chemistry; Spectroscopy; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Radiation; Electronic; Optical and Magnetic Materials

Optimal Design of Motor and Gear for Drives With High Acceleration by Consideration of Torque–Speed and Torque–Acceleration Product - Grotstollen, Horst (IEEE Transactions on Industry Applications)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Control and Systems Engineering

A Systematic Approach to Combined HW/SW System Test - Krupp, Alexander; Müller, Wolfgang (Proceedings of DATE’10)
Today we can identify a big gap between requirement specification and the generation of test environments. This article extends the Classification Tree Method for Embedded Systems (CTM/ES) to fill this gap by new concepts for the precise specification of stimuli for operational ranges of continuous control systems. It introduces novel means for continuous acceptance criteria definition and for functional coverage definition.
Keywords: System testing; Automatic testing; Object oriented modeling; Classification tree analysis; Automotive engineering; Mathematical model; Embedded system; Control systems; Electronic equipment testing; Software testing

Blue Phases: Prior Art, Potential Polar Effects, Challenges - Kitzerow, Heinz-Siegfried (Ferroelectrics)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Blue Phases: Prior Art, Potential Polar Effects, Challenges - Kitzerow, Heinz-Siegfried (Ferroelectrics)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

EXAFS as Powerful Analytical Tool for the Investigation of Organic-Inorganic Hybrid Materials - Gross, Silvia; Bauer, Matthias (Advanced Functional Materials)
Keywords: Electrochemistry; Condensed Matter Physics; Biomaterials; Electronic; Optical and Magnetic Materials

Elektromobilität — ein aktuelles Forschungsfeld insbesondere der Regelungstechnik - Kröger, Claus; Böcker, Joachim; Neiß, Konstantin (at - Automatisierungstechnik)
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

A zirconium methacrylate oxocluster as precursor for the low-temperature synthesis of porous zirconium(iv) dicarboxylates - Guillerm, Vincent; Gross, Silvia; Serre, Christian; Devic, Thomas; Bauer, Matthias; Férey, Gérard (Chem. Commun.)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Functional Chromium Wheel-Based Hybrid Organic-Inorganic Materials for Dielectric Applications - Di Noto, Vito; Boeer, Angelika B.; Lavina, Sandra; Muryn, Christopher A.; Bauer, Matthias; Timco, Grigore A.; Negro, Enrico; Rancan, Marzio; Winpenny, Richard E. P.; Gross, Silvia (Advanced Functional Materials)
Keywords: Electrochemistry; Condensed Matter Physics; Biomaterials; Electronic; Optical and Magnetic Materials

Continuous-variable quantum information processing - Andersen, U.L.; Leuchs, G.; Silberhorn, Christine (Laser & Photonics Reviews)
Keywords: Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Nanocrystals of [Cu3(btc)2] (HKUST-1): a combined time-resolved light scattering and scanning electron microscopy study - Zacher, Denise; Liu, Jianing; Huber, Klaus; Fischer, Roland A. (Chemical Communications)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Autonomous Sensor Nodes for Aircraft Structural Health Monitoring - Becker, Thomas; Kluge, Martin; Schalk, Josef; Tiplady, Keith; Paget, Christophe; Hilleringmann, Ulrich; Otterpohl, Tobias (IEEE Sensors Journal)
Keywords: Electrical and Electronic Engineering; Instrumentation

Efficient Antenna Design of Inductive Coupled RFID-Systems with High Power Demand - Reinhold, Christian; Scholz, Peter; John, Werner; Hilleringmann, Ulrich (Journal of Communications)
Keywords: Electrical and Electronic Engineering

Reflection of femtosecond pulses from soft X-ray free-electron laser by periodical multilayers - Ksenzov, D.; Grigorian, S.; Hendel, S.; Bienert, F.; Sacher, Marc; Heinzmann, U.; Pietsch, U. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Microemulsion approach to neodymium, europium, and ytterbium oxide/hydroxide colloids—Effects of precursors and preparation parameters on particle size and crystallinity - Rill, Christoph; Bauer, Matthias; Bertagnolli, Helmut; Kickelbick, Guido (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Dielectric layers for organic field effect transistors as gate dielectric and surface passivation - Diekmann, T.; Pannemann, C.; Hilleringmann, Ulrich (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials